Tinjauan Yuridis terhadap Penjual Eceran Bahan Bakar Minyak yang Tidak Memiliki Izin Usaha dalam Perspektif Hukum Perdata - Ramadhani, Nova; Ferianto,; Prasetiyo, Erik (Aufklarung: Jurnal Pendidikan, Sosial dan Humaniora, 2022)
Fuel Oil (BBM) is one of the commodities from natural resources of oil and gas which has an important role in the national economy so that in its management it must maximize the prosperity and welfare of the community. This fuel oil (BBM) is also a necessity that is very influential in any aspect used in the means of transportation. The regulations governing Oil and Gas are clear as regulated in Law Number 22 of 2001 concerning Oil and Gas. With the increasing demand for Oil Fuel (BBM), this opens up opportunities for business actors to run their businesses as gasoline retailers on the roadside. In this case, of course, the business actor must already have a license to do business as a form of legality. In fact, there are still many business actors selling fuel oil on the side of the road who do not have a business license and of course it is very detrimental to consumers. In Law Number 8 of 1999 concerning Consumer Protection, it is regulated about the rights of consumers to be protected and entitled to honest information, goods that are in accordance with what they should and are not cheated by the business actors themselves. The method used in this research is juridical-normative approach in the form of legislation (statue approach), conceptual approach (conceptual approach), and case approach (case approach). This study was conducted with the aim of finding out how the legality of a business license is against a fuel oil retailer on the roadside and also to find out how civil law enforcement is against a roadside fuel oil retailer without a business license.